Lycopene and Other Bioactive Compounds’ Extraction from Tomato Processing Industry Waste: A Comparison of Ultrasonication Versus a Conventional Stirring Method - Konstantinos Mavridis; Nikolaos Todas; Dimitrios Kalompatsios; Vassilis Athanasiadis; Stavros I. Lalas (Horticulturae)
The tomato (Lycopersicon esculentum) is a prominent fruit in Mediterranean countries with established biological activities for consumers. Given the widespread distribution of the fruit and its large production, the need to utilize the by-products seems imperative. With a view to valorizing the main carotenoid of tomato processing industry waste, lycopene, as well as other bioactive compounds (i.e., polyphenols), the optimization of a green extraction method involving ultrasound-assisted bath extraction (UBAE) was carried out. The results showed that the optimized UBAE technique achieved substantial yields of total carotenoids (420.8 μg of lycopene equivalents per gram of dry weight (dw)) and total polyphenols (2.62 mg of gallic acid equivalents per gram of dw). Flavonoid naringin (0.48 mg/g dw) and non-flavonoid coniferyl alcohol (0.32 mg/g dw) were the most abundant identified polyphenols. However, comparison with a conventional stirring extraction revealed that the latter technique marked double figures in all assays, including antioxidant activity assays. The study revealed that UBAE was not a preferable technique for recovering carotenoids because of the possible degradation of labile compounds found in tomato processing industry waste. Given that the extraction solvent was pure ethanol, the study established a foundation for the development of a unique lycopene-enriched product in the food industry. It is essential to conduct additional studies using alternative food-grade solvents or other environmentally friendly extraction methods.